EXISTENTIAL FULLNESS OF PERSONALITY IN LATE ADULTHOOD - Partyko, Tetiana (PSYCHOLOGICAL JOURNAL, 2019)
On the basis of empirical research the article presents the analysis of the psychological content of the levels of personality existential fullness in late adulthood (60+). Existential scale by А. Langle and К. Orgler, methodology of social and psychological adaptation by K. Rogers and R. Diamond, methodology of disharmony in interpersonal relations by S. Dukhnovsky were used. Respondents: 108 persons aged 60 to 84 (average age – 66,9 years). Three levels were identified: sufficient (26%, average age – 63,9 years), moderate (41,6%, average age – 67,8 years), insufficient (32,4%, average age – 68 years). Every fourth person belonged to the level with sufficient existential fullness. Their life is meaningful, they think it over well, take responsible decisions and implement them in life, they are well-adapted emotionally among their peers, build harmonious relations with the surrounding people. It is favored by experiencing emotional well-being. People who are at the moderate level of existential fullness make the majority. Their inner space is somewhat narrowed and emotional engagement in life is reduced. At the same time they are quite well adapted to the world and their relations with the other people in general are harmonious and stable which can be a significant resource for cognitive and emotional accessibility growth. Achievement of existential fullness depends on adaptability of a personality, acceptance of oneself and others, experiencing emotional comfort, internality and harmony of relations. Every third person is at the level of insufficient existential fullness. Cognitive and emotional accessibility is low: internal space of a personality is insufficient, and emotional engagement in life is poor. They are moderately adapted to the world, their relationship with other people are also moderately harmonious and stable. However, in comparison with other peers adaptability and harmoniousness are the lowest. These elderly people did not manage to fully understand their life, which accounts for the low responsibility for their own life. It is stated that for people with sufficient existential fullness the resource for existential problem resolution is their emotional comfort; for people with moderate fullness – emotional comfort, internality, growth of adaptive abilities, establishment of harmonious relations with the surrounding people, accepting oneself and others; for people with insufficient existential fullness – internality.